Perancangan Desain Mata Uang Kertas Rupiah sebagai Kasus Wacana Redenominasi - Suprayitno, Suprayitno (Bina Nusantara University, 2014)
According to Bank Indonesia, the currency redenomination is simplification by reducing the three-digit number zero, without reducing its value. Fundamental changes in the nominal rate of writing, become very urgent in terms of design drafting new bills. The process and method of creating the work is qualitative, ie, empirical studies of cultural phenomena in the creation of this work aimed at deepening the validity of the data, the researchers involved in the search for the data directly in the field. The way it can play a significant role in revealing and unravel the problem, in order to create connectivity in the creation of the work needs to be focused on the core message. The findings are contributions of renewable and creative solutions in the manufacture of paper currency design planning of Rupiahs, including the proposed vertical format that has never been applied to the design of paper currency of Rupiahs. Then the proposed implementation of security features barcode, which has advantages and superiority in facilitating the detection of counterfeit banknotes, will make digital counting faster and more accurate than manual.